Axial to transverse energy mixing dynamics in octupole-based magnetostatic antihydrogen traps - A Zhong; J Fajans; A F Zukor (New Journal of Physics)
The nature of the trajectories of antihydrogen atoms confined in an octupole minimum-B trap is of great importance for upcoming spectroscopy, cooling, and gravity experiments. Of particular interest is the mixing time between the axial and transverse energies for the antiatoms. Here, using computer simulations, we establish that almost all trajectories are chaotic, and then quantify the characteristic mixing time between the axial and transverse energies. We find that there are two classes of trajectories: for trajectories whose axial energy is higher than about 20% of the total energy, the axial energy substantially mixes within about 10 s, whereas for trajectories whose axial energy is lower than about 10% of the total energy, the axial energy remains nearly constant for 1000 s or longer.